The Implementation of the SOLE (Self-Organized Learning Environment) Learning Model in Answering Big Questions in Algebra Topics - Ana Uzla BatuBara; Tuful Zuchri Siregar (International Journal of Community Service Implementation, 2025)
The SOLE learning model facilitates students to learn independently through exploration and group discussion, with a focus on solving relevant and challenging problems. This community service activity aims to improve the competencies of both teachers and students in mathematics learning, particularly in algebra, through the implementation of the SOLE (Self-Organized Learning Environment) model based on Big Questions. The SOLE model is designed to encourage students to learn independently and collaboratively through open-ended questions that stimulate critical thinking and problem-solving skills. This activity was conducted at a partner junior high school, involving both teachers and students as participants in training and mentoring sessions. The methods employed in this program included the dissemination of the SOLE and Big Question concepts, training in lesson planning, and guided classroom implementation. The results of the activity showed an improvement in teachers' understanding of innovative teaching strategies, as well as positive responses from students, who demonstrated active engagement, increased curiosity, and better conceptual understanding of algebra. This community service initiative provides a tangible contribution to strengthening teachers’ capacity in designing meaningful instruction and in creating a learning environment that promotes student autonomy and creativity. The application of the SOLE model based on Big Questions has proven to be an effective approach to delivering mathematics instruction in a more contextualized and enjoyable manner.